Estudo do comportamento de conectores Crestbond em pilares mistos tubulares preenchidos com concreto - Otavio Prates Aguiar (2015)
The Brazilian Standard Design of steel and composite structures for buildings using hollow sections - ABNT NBR 16239:2013 proposes the use of screws or Stud Bolts as shear connectors in composite columns. Recently, researchers from Universidade Federal de Minas Gerais - UFMG proposed to use, in this type of column, the Crestbond connector, which was originally designed for use in composite beams and consists of a puzzle shaped steel plate. To study the behavior of this connector when used in composite columns with concrete filled tubes, these researchers performed a series of push tests that seek to recreate the conditions observed in this kind of columns. This work is dedicated to simulate some of these push tests through finite element method in order to elucidate the behavior of this connector on these columns. For this, the push tests conducted by these researchers as well as the results achieved by them were studied, and then a numerical model that aims to recreate the characteristics of these tests was proposed. Finally, an effort to validate the numerical model through a comparative analysis of the results was conducted. Throughout this model validation effort, important mechanisms and behavior patterns of the connector were identified, concerning aspects such as stiffness, ultimate strength and the force that leads to loss of linearity of the force versus slip curve. Additionally, a number of considerations were made regarding the stiffness of the Crestbond and how the conditions of the concrete within the hollow section interfere in this property.